The application of Arcs Motivational Model In Massive Open Online Course (MOOC) / Erny Arniza Ahmad - Ahmad, Erny Arniza (UiTM Press, 2019)
Massive Online Open Course (MOOC) is an emerging practice in open learning. It also becomes an alternative way of delivering interactive teaching and learning. Malaysian Education Blueprint for Higher Education (2015-2025) has discussed MOOC under the 9th Shift called "Globalized Online Learning". In this Shift, Ministry of Education declares Malaysia's aims to leverage on MOOC as a way to take advantage of technology to improve quality and widen access to education (Ministry of Education, 2015).